Method of tendering (maintenance S.K Changkat Jong) / Farah Asyikin Mohamad Fadzilah - Mohamad Fadzilah, Farah Asyikin (2021)
Tendering is one on an important process in construction in this report, it will explain the method of tendering for a construction for the expected costs. As it can be explained specifically and also to complete the report contents. The main objective for this report is to explain the type of tendering, the method of tendering and some of the typical problems in tendering process. Other than that, this report will content and explain some of the types in tendering. As for the method, there’s three of them which is observation, referencing journal, book and internet and interviewing. After all for open tendering, it is the easiest method in tendering. However, there is few problems for this type of tendering. As a conclusion, knowing the proper method of tendering is important especially for a contractor to gain more project for their company in the future.